A Randomized Controlled Trial Evaluating Negative Pressure Therapy (NPT) to Reduce Wound Complications Following Major Lower Extremity Amputation - Paul J. DiMuzio; Cara M. Staley; Federico Biscetti; Dawn M. Salvatore; Babak Abai; Michael J. Nooromid; Roberto G. Aru; Scott Keith; Romeo B. Mateo; Nii-Kabu Kabutey; Ellen D. Dillavou (Annals of Surgery, 2026)
Objective: This study hypothesizes that negative pressure therapy (NPT) reduces wound-healing complications following major amputation. Background: Major lower extremity amputation carries a high incidence of incisional complications. NPT reduces these complications in other areas of the body, suggesting a benefit following amputation. Methods: Patients undergoing above- or below-knee amputation (AKA, BKA) were randomized in this multi-institution study into receiving NPT versus standard dressing. The primary endpoint was any wound complication within 30 days of surgery; secondary endpoints included reoperation, readmission, and length of stay. Post hoc analyses were performed in patients considered high risk for wound complications. Results: The overall 30-day mortality rate was 3.4%. The wound complication rate for the NPT group was 19.4% (n=134) compared with 24% for controls (n=129; RR=0.80; 95% CI: 0.51, 1.26; P =0.339). No significant difference was observed for reoperation (3.7% vs. 8.5%, RR=0.83), readmission (9% vs. 11.6%, RR=0.77), or length of stay (10 vs. 9.3 d, RR=1.1). Post hoc analyses suggested a reduction in complications using NPT in people without diabetes (9.8% vs. 27.6%, RR=0.36), those with end-stage renal disease (ESRD; 23.1% vs. 37.5%, RR=0.66), patients with obesity (18.2% vs. 26.7%, RR=0.65), and those presenting without tissue loss (3.6% vs. 35.5%, RR=0.10). Conclusions: Wound complications remain a significant problem following major lower extremity amputation, leading to reoperation, readmission, and increased length of stay. NPT does not significantly reduce the overall wound complication rate. Future studies should focus on high-risk subgroups that may benefit from this therapy.